2017
DOI: 10.1155/2017/2019802
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Helicobacter pylori Eradication with Vonoprazan, Clarithromycin, and Metronidazole in Patients Allergic to Penicillin

Abstract: Aim To assess the efficacy of 7-day first-line Helicobacter pylori eradication with vonoprazan (VPZ), clarithromycin (CAM), and metronidazole (MNZ) in patients with penicillin allergy. Methods Patients with penicillin allergy, diagnosed with Helicobacter pylori infection and did not have history of Helicobacter pylori eradication, were eligible for the study. Twenty patients were prospectively treated with 20 mg VPZ twice daily, 200 or 400 mg CAM twice daily, and 250 mg MNZ twice daily for 7 days. We also coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…We confirmed the superiority of the V‐AC compared with PPI/AMPC/CAM (PPI‐AC) for first‐line eradication in a multicenter prospective study, whereas no significant differences were observed between VPZ/AMPC/MNZ (V‐AM) and PPI/AMPC/MNZ (PPI‐AM) for second‐line eradication . In addition, in a retrospective study and in our prospective study, an excellent grading eradication rate with VPZ/CAM/MNZ (V‐CM) or VPZ/MNZ/STFX (V‐MS) was reported in patients allergic to penicillin. These data suggest that a VPZ‐based third‐line regiment could improve the eradication rate compared with conventional PPI‐based regimens.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We confirmed the superiority of the V‐AC compared with PPI/AMPC/CAM (PPI‐AC) for first‐line eradication in a multicenter prospective study, whereas no significant differences were observed between VPZ/AMPC/MNZ (V‐AM) and PPI/AMPC/MNZ (PPI‐AM) for second‐line eradication . In addition, in a retrospective study and in our prospective study, an excellent grading eradication rate with VPZ/CAM/MNZ (V‐CM) or VPZ/MNZ/STFX (V‐MS) was reported in patients allergic to penicillin. These data suggest that a VPZ‐based third‐line regiment could improve the eradication rate compared with conventional PPI‐based regimens.…”
Section: Introductionsupporting
confidence: 82%
“…28,29 The safety of the V-AS was confirmed using the same questionnaire used to demonstrate the safety of V-AC, V-AM, and V-CM. 12,14,21 These results support the superiority of VPZ-based regimens for eradicating H. pylori.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A small study assessing regimens including vonoprazan for penicillin‐allergic patients demonstrated an eradication rate of 92.9% for patients who received clarithromycin‐metronidazole‐vonoprazan which far surpassed the 54.2% achieved by PPI‐based therapies . Triple therapy with vonoprazan, clarithromycin, and metronidazole was well tolerated and effective for eradicating H. pylori in patients allergic to penicillin …”
Section: Vonoprazanmentioning
confidence: 99%
“…57 Triple therapy with vonoprazan, clarithromycin, and metronidazole was well tolerated and effective for eradicating H. pylori in patients allergic to penicillin. 58 Safety of new medication is always a concern. One study assessing vonoprazan triple therapy in children found adverse effects (rash/GI disturbance) in 21.1%.…”
Section: Vonopr a Z Anmentioning
confidence: 99%